A Novel Approach for More Effective Emergency Equipment Storage: The Task-Based Package-Organized Neonatal Emergency Backpack - Sommer, Lorenz; Huber-Dangl, Mercedes; Klebermaß-Schrehof, Katrin; Berger, Angelika; Schwindt, Eva (Frontiers in Pediatrics, 2021)
Objectives: To evaluate a new task-based package-organized (TPO) neonatal emergency backpack and to compare it to the classical (ABC- and material-based) backpack. Methods: Simulation-based assessment of time to retrieve equipment for three different tasks [intraosseous access (IO), intubation and adrenaline administration] using the TPO and the classical emergency backpack was compared. Results: Equipment retrieval times for the three tasks were assessed for 24 nurses (12 intermediate care, 12 intensive care) and were significantly faster in the TPO than in the classical backpack (IO 33 vs. 75 s, p < 0.001; intubation 53 vs. 70 s, p = 0,001; adrenaline 22 vs. 45 s, p < 0.001). The number of missing items was significantly lower using the TPO backpack for IO and adrenaline retrieval (IO 0,9 vs. 2,3 items, p < 00001, adrenaline 0.04 vs. 1, p < 0.001) but not for intubation equipment (0.9 vs. 1, not significant). The subjective rating of overall clearness was significantly higher for the TPO compared with the classical backpack (5,9 vs. 3,5, p < 0.001). Conclusion: Task-based package organization of neonatal emergency backpacks is feasible and might be superior to ABC-/material-oriented storage.